Gain design and verification of autopilot control loops for UVAs - Huang, Qian. (2013)
In this master thesis, autopilot control system of a UAV has been developed. Before starting the control system design, general concepts of system response have been reviewed. This whole work is divided into two parts. In the first part, autopilot structures have been developed and its control gains have been computed through design routine based on linear state space models of UAV and requirements of system response. In the second part, verifications of designed autopilot system are implemented for both linear and non-linear simulation models. In the end, conclusions about the suitability and relevance of the designed control system and achieved performance have been discussed.